2017
DOI: 10.17219/acem/65478
|View full text |Cite
|
Sign up to set email alerts
|

The neuroprotective effect of N-acetylcysteine in spinal cord-injured rats

Abstract: Background. Spinal cord injury (SCI) is an important cause of impairment of sensory and motor nerve function. It has been shown that free-radical species play an important role in the pathogenesis of acute tissue trauma after SCI. There are no proven pharmacological therapies that provide neuroprotection and stimulate axonal growth after trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
(26 reference statements)
0
8
0
Order By: Relevance
“…Furthermore, NAC has been reported to possess antioxidant properties by scavenging reactive oxygen species (ROS) and also inhibit the activity of cyclooxygenase-2 and membrane lipid peroxidation induced by inflammation [18,19]. Coombes et al suggest that NAC has reno-protective activities in chronic kidney disease [20] and neuro-protective effect on spinal cord-injury [21]. Preliminary data in rat model revealed that oral treatment with high-dose NAC during early silica exposure can ameliorate the activity of proinflammatory cytokines, down-regulating ROS, and mitochondrial apoptosis signaling, thus attenuating subsequent lung fibrosis, suggesting the potential of NAC in the treatment for silica-induced lung fibrosis [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, NAC has been reported to possess antioxidant properties by scavenging reactive oxygen species (ROS) and also inhibit the activity of cyclooxygenase-2 and membrane lipid peroxidation induced by inflammation [18,19]. Coombes et al suggest that NAC has reno-protective activities in chronic kidney disease [20] and neuro-protective effect on spinal cord-injury [21]. Preliminary data in rat model revealed that oral treatment with high-dose NAC during early silica exposure can ameliorate the activity of proinflammatory cytokines, down-regulating ROS, and mitochondrial apoptosis signaling, thus attenuating subsequent lung fibrosis, suggesting the potential of NAC in the treatment for silica-induced lung fibrosis [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in rats using NAC or NACA to manage SCI have found beneficial therapeutic effects. 8 , 9 , 27 , 28 , 48 , 49 In this study, NACA was first given to naïve mice to reproduce a previously published dosing strategy that increases cellular GSH to demonstrate its potential for augmenting GSH within the spinal cord. After demonstrating the efficacy of our approach in naïve mice, both 4- and 14-MO mice received SCI and were treated with NACA, which did augment spinal GSH and improved the GSH/GSSG redox ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting GSH dysfunction after SCI has been performed by providing cysteine analogs such as n-acetylcysteine (NAC) or a more recently developed n -acetylcysteine amide (NACA) which has better bioavailability within the spinal cord ( Kamencic et al, 2001 ; Hanci et al, 2010 ; Karalija et al, 2012 , 2014 ; Patel et al, 2014 ; Guo et al, 2015 ; Olakowska et al, 2017 ; Stewart et al, 2022b ). Treating SCI in rats with NAC or NACA restores cellular levels of GSH, protects against oxidative stress, and improves mitochondrial, behavioral, and histopathological outcomes ( Kamencic et al, 2001 ; Hanci et al, 2010 ; Karalija et al, 2012 , 2014 ; Patel et al, 2014 ; Guo et al, 2015 ; Olakowska et al, 2017 ).…”
Section: Aging In Animal Modelsmentioning
confidence: 99%
“…Targeting GSH dysfunction after SCI has been performed by providing cysteine analogs such as n-acetylcysteine (NAC) or a more recently developed n -acetylcysteine amide (NACA) which has better bioavailability within the spinal cord ( Kamencic et al, 2001 ; Hanci et al, 2010 ; Karalija et al, 2012 , 2014 ; Patel et al, 2014 ; Guo et al, 2015 ; Olakowska et al, 2017 ; Stewart et al, 2022b ). Treating SCI in rats with NAC or NACA restores cellular levels of GSH, protects against oxidative stress, and improves mitochondrial, behavioral, and histopathological outcomes ( Kamencic et al, 2001 ; Hanci et al, 2010 ; Karalija et al, 2012 , 2014 ; Patel et al, 2014 ; Guo et al, 2015 ; Olakowska et al, 2017 ). Owing to a pre-existing decrease in GSH with older age, as well as evidence of more ROS damage accumulating in older SCI-mice ( Zhang et al, 2016 , 2019 ; Stewart et al, 2021b ), we predicted that NACA treatment would have a robust protective effect in 14- compared to 4-month mice.…”
Section: Aging In Animal Modelsmentioning
confidence: 99%